ANALYSIS OF ATM SERVICE QUALITY ON CUSTOMER RETENTION: CASE STUDY OF MSME ATM USERS IN EAST PRIANGAN - Reni Sumarni; Lina Marlina (International Journal Multidisciplinary Science, 2024)
Automation is essential for Micro, Small, and Medium Enterprises (MSMEs) in a competitive business era to understand and implement customer retention strategies to survive and grow. This study aims to describe ATM Service Quality and customer retention among MSMEs using ATMs and analyze the influence of reliability, comfort, safety, convenience, and fulfillment variables on customer retention. The research method uses a quantitative approach with descriptive and exploratory survey methods. The research subjects were SMEs using ATMs in East Priangan, with the research object being ATM service quality and customer retention. Data was collected through questionnaires and observations using random sampling techniques. The statistical analysis results using Partial Least Squares Structural Equation Modeling (PLS-SEM) show high reliability in variable measurement and adequate discriminant validity. The findings indicate that the structural model indicates that reliability and convenience do not significantly affect customer retention, while security and convenience play an essential role. The implication is that it is essential to focus on the security and convenience aspects of ATM services to enhance customer retention strategies amidst intense business competition. These results provide in-depth and relevant insights, supporting the development of effective strategies for MSMEs, increasing the adoption of digital financial services and keeping customers away from the competition. .